Acid-binding type ultraviolet wavelength conversion resin master batch as well as preparation method and application thereof

By using acid-bound ultraviolet wavelength conversion resin masterbatch in photovoltaic packaging film, the problem of performance attenuation of photovoltaic modules under ultraviolet light irradiation is solved, and good acid-bound and anti-PID performance is achieved.

CN119859343APending Publication Date: 2025-04-22NINGBO EXCITON TECH +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510156624.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The performance of existing photovoltaic modules is attenuated under ultraviolet light, and the acid binding performance of the packaging film is insufficient, which affects the long-term high-reliability of the modules.

Method used

Using acid-bound ultraviolet wavelength conversion resin masterbatch, a photovoltaic packaging film with good light transmittance and acid-bound properties is prepared by adding acid-bound ultraviolet light converter and auxiliary agent to the vinyl resin.

Benefits of technology

It improves the utilization of ultraviolet light by photovoltaic cells, reduces the occurrence of cell cracks, and has good anti-PID performance and weather resistance under humid and heat aging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to an acid-binding type ultraviolet wavelength conversion resin master batch and a preparation method and application thereof, the main component of the master batch is an acid-binding type ultraviolet wavelength conversion compound containing double functional units, and the master batch can convert ultraviolet light into blue light and weaken the aging of a component at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optoelectronic technology, and in particular to an acid-bound ultraviolet wavelength conversion resin masterbatch, and a photovoltaic cell encapsulation adhesive film comprising the masterbatch. Background Art

[0002] Solar energy is one of the main renewable energy sources, with the characteristics of wide source, clean and harmless, and sustainable. The energy of solar radiation is mainly concentrated in 300nm-2400nm, which can be generally divided into ultraviolet light, visible light and infrared light. In the solar spectrum, the frequency of ultraviolet light is higher than that of visible light, and it can be divided into four types: ultraviolet A (wavelength 380nm-320nm, low frequency long wave), ultraviolet B (wavelength 320nm-280nm, medium frequency medium wave), ultraviolet C (wavelength 280nm-100nm, high frequency short wave), and ultraviolet D (100nm-10nm, ultra-high frequency).

[0003] When sunlight is incident on a solar cell module, due to the limitation of the wavelength response of the solar cell material itself, the solar cell can only absorb a part of the light of a specific wavelength. Ultraviolet light exposure will cause changes in the power generation of silicon solar modules. For example, dye-sensitized solar cells can have a reduced transmittance under ultraviolet light, thus affecting the photovoltaic power; the silicon-hydrogen bonds in the heterojunction cell structure are also more susceptible to damage by ultraviolet light, resulting in serious carrier recombination and low photovoltaic power; a study published by the US Renewable Energy Testing Center pointed out that TOPCon (Tunnel Oxide Passivated Contact) cell modules may be at risk of premature degradation after being affected by ultraviolet radiation.

[0004] In the new generation of high-efficiency battery technology, a variety of battery technologies have emerged rapidly, among which TOPCon battery modules have developed the fastest. Compared with traditional batteries, TOPCon battery modules have a more complex structure, and the silver-aluminum paste used is also more susceptible to corrosion. In addition, when photovoltaic modules are installed and applied in real environments, they will be affected by the atmospheric environment, mechanical loads of storms, wind and sand impact, rain and dew corrosion, etc. Therefore, in order to achieve the effect of high power generation efficiency, the industry has put forward higher requirements for the encapsulation film used in photovoltaic modules. Among them, EVA encapsulation film has received more attention. Due to its special structure, EVA resin may produce free acidic substances, which will affect the conductivity of the battery. Therefore, it is of great significance to reduce the production of acetic acid in EVA film and protect photovoltaic modules in a hot and humid environment to achieve long-term high reliability.

[0005] For the performance attenuation of components caused by ultraviolet light, a feasible solution is to add light conversion materials to the encapsulation film to convert the ultraviolet light with higher energy in sunlight into usable visible light. Patents (CN105308113B, CN105684163B, CN114854316A, CN117431022A, CN117720474B) report the technology of using ultraviolet light conversion materials to convert ultraviolet light to a certain extent, thereby protecting the ultraviolet attenuation of components, but the light conversion materials in these reports only have a single light conversion function. If the corresponding film water vapor permeability is reduced, acid binding and other properties are to be achieved, it is also necessary to add other multiple additives, however, the polarity of vinyl resin materials is relatively low, especially the more additives added to POE resin, the easier it is to cause the migration and precipitation of additives.

[0006] Patents (CN114806457A, CN108250576A, CN101542748B) report the use of inorganic particles or resin modification technology to increase the service life of photovoltaic encapsulation films and solve the problem of degradation of encapsulation effect after aging of the film material. However, the technologies in these patents either use inorganic particles with poor compatibility with organic resins, resulting in low transmittance of the film, which in turn affects component performance; or use a multi-step polymerization process, with multiple auxiliary agent production routes and complicated routes.

[0007] Patents (CN108250576A, CN118240491A, CN119081573A, CN116082984A) also reported amino-modified MOF materials, stearate compounds, or highly alkaline organic amine compounds as acid binders. However, these acid binders either only have a single acid binder function, and after adding, not only the amount of additives used in the film is increased, but also the initial power generation of the component is not improved; or the synthesis route is long, resulting in high cost of use; or the highly alkaline organic amine compounds affect the performance of the film. Summary of the invention

[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide an acid-binding ultraviolet wavelength conversion resin masterbatch and a preparation method and application thereof. The encapsulation film of the present invention has good light transmittance and good acid-binding performance, and also improves the problem of battery utilization of ultraviolet light, reduces the occurrence of hidden cracks in battery cells during the lamination process, and has good anti-PID performance under wet heat aging conditions.

[0009] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, an acid-binding ultraviolet wavelength conversion resin masterbatch is provided. The acid-binding ultraviolet wavelength conversion resin masterbatch comprises, by weight percentage, 80 to 99.8% of vinyl resin, 0.01 to 15% of acid-binding ultraviolet light conversion agent, and 0.18 to 10% of auxiliary agent.

[0010] Furthermore, the vinyl resin is a high molecular thermoplastic polymer material with a melting temperature of 65°C to 120°C, or 70°C to 115°C, or 80°C, 90°C, 100°C, 105°C, or 110°C, including but not limited to polyethylene, polypropylene, or copolymers of ethylene and α-olefins, or copolymers of ethylene and one or more of vinyl acetate, acrylic acid, acrylic esters, methacrylic acid, methacrylates, maleic anhydride, and glycidyl methacrylate.

[0011] Preferably, examples of α-olefins include α-olefins having 2 or 4 to 20 carbon atoms, such as propylene, one or more of ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene and 4-methyl-1-pentene; or α-olefins having 6, 8, 10, 12, 14, 15, 16, 18 carbon atoms. The above types of vinyl polymers have better processing properties and suitable fluidity. More preferably, the vinyl resin is one or more of ethylene and vinyl acetate copolymers, ethylene and 1-butene copolymers, and ethylene and 1-octene copolymers.

[0012] Furthermore, the content of the vinyl resin is 82-99.5%, or 85%, 88%, 90%, 92%, 94%, 96%, or 98%.

[0013] Furthermore, the acid-binding type ultraviolet light conversion agent is a triazine derivative containing an active group, and its general structural formula is as follows:

[0014]

[0015] Wherein, R1, R2, and R3 are each independently selected from the substituents of amino, amino-substituted or unsubstituted C1-C10 (or C2, C4, C5, C7, C8, C9) hydrocarbon groups, Any one of the above, wherein R4 is selected from any one of hydrogen, amino, amino-substituted or unsubstituted C1-C10 (or C2, C4, C5, C7, C8, C9) hydrocarbon groups.

[0016] Furthermore, the content of the acid-binding ultraviolet light conversion agent is 0.05-14%, or 0.5%, 1%, 3%, 5%, 7%, 9%, 11%, 12%, or 13%.

[0017] Furthermore, the content of the auxiliary agent is 0.5-9.5%, or 1%, 2%, 5%, 7%, 8%, 9%.

[0018] Furthermore, the auxiliary agent is one or a mixture of two or more of an initiator, a cross-linking agent, a coupling agent, an antioxidant, and a stabilizer.

[0019] Furthermore, the weight percentage of the initiator is 0.005-5%, or 0.1-4.5%, or 0.5%, 1%, 2%, 3%, or 4%.

[0020] Furthermore, the weight percentage of the cross-linking agent is 0.005-5%, or 0.1-4.5%, or 0.5%, 1%, 2%, 3%, or 4%.

[0021] Furthermore, the weight percentage of the coupling agent is 0.005-5%, or 0.1-4.5%, or 0.5%, 1%, 2%, 3%, or 4%.

[0022] Furthermore, the weight percentage of the antioxidant is 0.005-5%, or 0.1-4.5%, or 0.5%, 1%, 2%, 3%, or 4%.

[0023] Furthermore, the weight percentage of the stabilizer is 0.005-5%, or 0.1-4.5%, or 0.5%, 1%, 2%, 3%, or 4%.

[0024] Furthermore, the initiator is selected from one or two or more of a cationic polymerization initiator, a free radical polymerization initiator, an anionic polymerization initiator or a coordination polymerization initiator.

[0025] The preferred free radical polymerization initiator may be any one or two or more of azobisisobutyronitrile, azobisisoheptylnitrile, azobisisovaleronitrile, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, tert-butylperoxyisopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butylperoxycarbonic acid-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, and tert-amyl peroxy-2-ethylhexyl carbonate.

[0026] Furthermore, the crosslinking agent is a substance containing multiple functional groups in the structure, such as organic dibasic acid, polyol, etc., or multiple unsaturated double bonds, which generates chemical bonds between linear molecules, connects the linear molecules together, forms a network structure, and improves the strength and elasticity of the polymer material. The crosslinking agent can be added together with the monomer, and crosslinking occurs when the polycondensation (or polymerization) reaches a certain degree, so that the product becomes an insoluble crosslinked polymer; or a certain number of functional groups (or double bonds) can be retained in the linear molecules, and then specific substances are added for crosslinking.

[0027] The crosslinking agent used in the present invention is selected from substances containing multiple unsaturated double bonds, and can be the following compounds: triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate Any one or more of acrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tri(allyloxy)-1,3,5-triazine, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, bisphenol A ethoxylate diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate.

[0028] Furthermore, the coupling agent is a substance with two functional groups of different properties. The biggest feature of its molecular structure is that it contains two groups with different chemical properties. One is an inorganic-friendly group that is easy to react chemically with the surface of inorganic substances; the other is an organic-friendly group that can react chemically with synthetic resins or other polymers or generate hydrogen bonds and dissolve in them. The coupling agent is called a "molecular bridge" and is used to improve the interface between inorganic and organic substances, thereby greatly improving the performance of the composite material.

[0029] Furthermore, according to the chemical structure and composition of the coupling agents, they are divided into four categories: organic chromium complexes, silanes, titanates and aluminate compounds.

[0030] The coupling agent used in the present invention is selected from silane coupling agents, and can be any one or more of the following compounds: vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxide tert-butyl silane, vinyl triacetoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidyloxypropyl trimethylsilane, and 3-aminopropyl trimethylsilane.

[0031] Furthermore, the antioxidant is used to prevent polymer materials from losing strength and toughness due to oxidative degradation. Ultraviolet radiation can cause chemical bonds in polymers to break and produce free radicals. The generated free radicals react with oxygen to produce peroxy radicals, which can cause further damage in a chain reaction. Vinyl polymers, such as polyethylene and polypropylene, are more stable than free radicals of primary carbon atoms due to the presence of secondary carbon or tertiary carbon atoms in the repeating units or side chains of the polymers, causing cracks or degradation on the exposed surface of the polymer material. According to the mechanism of action of antioxidants, they are divided into free radical absorbing antioxidants, oxygen scavenging antioxidants, metal ion chelating stabilized antioxidants, singlet oxygen capturing antioxidants, biological antioxidants and the like.

[0032] The antioxidant used in the present invention is selected from free radical absorbing antioxidants, and can be any one or two or more of the following compounds: tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester, bis(3,5-di-tert-butyl-4-hydroxyphenylpropionyl)hydrazine, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, distearyl thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), didodecyl thiodipropionate, nonyl-N-(nonylphenyl)aniline, and 4,6-bis(octylthiomethyl)-o-cresol.

[0033] Furthermore, after absorbing ultraviolet rays, polymer products can cause self-oxidation and degradation of polymers, destroy the chemical bonds of polymers, break them, and crosslink them, resulting in deterioration of the appearance and physical and mechanical properties of polymer products such as color, reduced strength, and shortened life. Light stabilizers can shield or absorb the energy of ultraviolet rays, quench singlet oxygen, and decompose hydroperoxides into inactive substances, so that polymers can eliminate or slow down the possibility of photochemical reactions under light radiation, and prevent or delay the process of light aging. Light stabilizers can be divided into light shielding agents, ultraviolet absorbers, free radical scavengers, and hydroperoxide decomposers according to their mechanism of action.

[0034] The light stabilizer used in the present invention is selected from bis-2,2,6,6-tetramethylpiperidinol sebacate, 2,4-dichloro-6-(4-morpholinyl)-1,3,5-triazine, bis-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate, a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, a composite of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate / methyl-1,2,2,6,6-pentamethyl-4-piperidinyl sebacate or a composite of succinic acid and (4-hydroxy-2,2,6,6-tetramethyl-1- any of 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-octyloxyphenol, 2-(2-hydroxy-5-methylphenyl)benzotriazole, N,N'-dicyclohexylcarbodiimide, N,N'-di(2,6-diisopropylphenyl)carbodiimide, N,N'-diisopropylcarbodiimide, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride.

[0035] The present invention also provides a method for preparing the acid-binding ultraviolet wavelength conversion resin masterbatch, which can be a common type in the art, such as: mixing through mixing equipment such as an internal mixer, an open mixer, a twin-screw extruder, etc. to form a composition, and the composition is finally granular, which can also be called a masterbatch. In simple terms, the preparation of the acid-binding ultraviolet wavelength conversion resin masterbatch firstly uniformly mixes the vinyl resin, the acid-binding light conversion agent, the light stabilizer, the antioxidant, etc., and then puts the mixed materials into a device with a mixing function, mixes them under a suitable temperature and pressure, and extrude them into granular materials.

[0036] According to another aspect of the present invention, there is provided an acid-binding ultraviolet wavelength conversion composition, comprising 70-98% of vinyl resin, 1-15% of acid-binding ultraviolet light conversion resin masterbatch, and 1-7% of auxiliary agent.

[0037] Furthermore, the content of the vinyl resin is 75-95%, or 80%, 85%, 88%, 90%, 92%, or 94%.

[0038] Further, the auxiliary agent is a mixture of one or more of the aforementioned initiator, crosslinker, coupling agent, antioxidant, and stabilizer; the weight percentage of the initiator is 0.005-5%, and / or the weight percentage of the crosslinker is 0.005-5%, and / or the weight percentage of the coupling agent is 0.005-5%, and / or the weight percentage of the antioxidant is 0.005-5%, and / or the weight percentage of the stabilizer is 0.005-5%. The specific preferred type is the same as the aforementioned auxiliary agent, and will not be repeated here.

[0039] According to another aspect of the present invention, a photovoltaic encapsulation film is provided, which is a single-layer structure or a multi-layer structure, and the material of at least one layer of the encapsulation film is the above-mentioned acid-bound ultraviolet wavelength conversion composition.

[0040] Furthermore, the method for preparing the photovoltaic encapsulation film can adopt the commonly used processes in the field. For example, each layer of the encapsulation film can be mixed separately, and the masterbatch, raw material particles, additives, etc. are weighed in proportion and mixed evenly in a mixing kettle as a certain component, and the aforementioned vinyl resin, acid-binding ultraviolet wavelength conversion resin masterbatch, and additives are mixed evenly in a mixing kettle in a certain ratio as another component, and are plasticized in a single-screw or twin-screw extruder with a set temperature and then extruded separately, distributed by a distributor, shaped by a die head, and embossed by a roller to obtain a multilayer photovoltaic encapsulation film; for example, only vinyl resin, acid-binding ultraviolet wavelength conversion resin masterbatch, and additives can be used. Mixed evenly in a mixing kettle in a certain ratio, and then plasticized in a single-screw or twin-screw extruder with a set temperature and then extruded separately to obtain a single-layer photovoltaic encapsulation film.

[0041] The present invention also provides an acid-binding type ultraviolet light conversion agent used in photovoltaic encapsulation film, which is a triazine derivative containing an active group, and its general structural formula is as follows:

[0042]

[0043] Wherein, R1, R2, and R3 are each independently selected from the substituents of amino, amino-substituted or unsubstituted C1-C10 (or C2, C4, C5, C7, C8, C9) hydrocarbon groups, Any one of the above, wherein R4 is selected from any one of hydrogen, amino, amino-substituted or unsubstituted C1-C10 (or C2, C4, C5, C7, C8, C9) hydrocarbon groups.

[0044] The present invention also provides a method for preparing the acid-bound ultraviolet light-converting agent used for photovoltaic encapsulation adhesive film, which is obtained by using a triazine derivative containing a halogen group as a raw material through a substitution reaction under alkaline conditions and the presence of a catalyst.

[0045] The present invention also provides an application of an acid-binding type ultraviolet light conversion agent in a photovoltaic encapsulation film. The acid-binding type ultraviolet light conversion agent is a triazine derivative containing an active group, and its general structural formula is as follows:

[0046]

[0047] Wherein, R1, R2, and R3 are each independently selected from the substituents of amino, amino-substituted or unsubstituted C1-C10 (or C2, C4, C5, C7, C8, C9) hydrocarbon groups, Any one of the above, wherein R4 is selected from any one of hydrogen, amino, amino-substituted or unsubstituted C1-C10 (or C2, C4, C5, C7, C8, C9) hydrocarbon groups.

[0048] By applying the technical solution of the present invention, compared with the prior art, the present invention has at least the following beneficial effects: the photovoltaic encapsulation film prepared by using the acid-binding ultraviolet wavelength converter can maintain a high light transmittance and good acid-binding performance, while also improving the problem of battery utilization of ultraviolet light and reducing the occurrence of hidden cracks in the battery cell during the lamination process. The film has good anti-PID performance and weather resistance under wet heat aging conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0050] Figure 1 20 is a schematic diagram of a three-layer co-extruded film structure according to an embodiment of the present invention, 20 is one layer of the film, 21 is another layer of the film, and 22 is the third layer of the film.

[0051] Figure 2 This is the infrared spectrum of the acid-binding ultraviolet conversion agent A prepared in Example 1.

[0052] Figure 3 Schematic diagram of the structure of a double-glass solar cell assembly according to an embodiment of the present invention; the solar cell assembly includes a glass plate 30, a packaging film 31, a cell array 32, a packaging film 33 and a glass plate 34 stacked in sequence. DETAILED DESCRIPTION

[0053] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the following will be combined with the preferred embodiments of the present invention and described in detail as follows:

[0054] It should be noted that the illustrative embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. The features in the embodiments and the embodiments in this application can be combined with each other. The present invention will be described in detail below through specific cases and in combination with embodiments. The raw materials used in the following embodiments are all commercially available products.

[0055] Example 1

[0056]

[0057] Preparation of acid-binding ultraviolet light-converting agent A: 2,4,6-trichloro-1,3,5-triazine (3.01 g), 4-tert-butylphenylboronic acid (3.48 g), tetrakis(triphenylphosphine)palladium (0.38 g), potassium carbonate (5.62 g), toluene (50 ml) and water (10 ml) were added to a three-necked glass flask, fully degassed with nitrogen several times, and filled with nitrogen, heated to 95°C, and reacted for 30 hours under stirring. The reaction solution was cooled to room temperature, then washed and extracted with dichloromethane and saturated sodium chloride aqueous solution, and then the organic phase was dried with anhydrous sodium sulfate, the solvent was removed under reduced pressure, and the obtained solid was dispersed with chloroform, and separated with a silica gel column (petroleum ether / ethyl acetate) to obtain 3.71 g of the product (yield 80.8%).

[0058] 2,4-dichloro-6-tert-butylphenyl-1,3,5-triazine (3.01 g), 4-aminophenylboronic acid pinacol ester (5.59 g), tetrakis(triphenylphosphine)palladium (0.25 g), potassium carbonate (3.67 g), tetrahydrofuran (50 ml) and water (10 ml) were added to a three-necked glass flask, fully degassed with nitrogen several times, and filled with nitrogen, heated to 90°C, and reacted for 30 hours under stirring. The reaction solution was cooled to room temperature, then washed and extracted with dichloromethane and saturated sodium chloride aqueous solution, and then the organic phase was dried with anhydrous sodium sulfate, the solvent was removed under reduced pressure, and the obtained solid was dispersed with chloroform, filtered, and then recrystallized and purified to obtain 3.71 g (yield 82.3%) of acid-bound ultraviolet light conversion agent A.

[0059] Figure 1 The infrared spectrum of the acid-binding ultraviolet light conversion agent A is shown, from which the main absorption peaks of the triazine ring and the amino group can be seen.

[0060] Masterbatch preparation: Acid-binding ultraviolet light conversion agent A and EVA particles with a melt index of 25 g / 10 min and a vinyl acetate content of 28% were fully mixed in a mass ratio of 10:90, melt-plasticized and extruded into granules at a temperature of 95° C. using a twin-screw extruder to prepare a 10% concentration of acid-binding ultraviolet light conversion agent masterbatch 1.

[0061] Film preparation: Weigh 5 parts of acid-bound UV conversion agent masterbatch 1, 93 parts of Sulbang EVA resin, 0.51 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.53 parts of triallyl cyanurate, 0.25 parts of vinyl triacetoxy silane, 0.32 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 0.43 parts of bis-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate, and place them in a mixing kettle for stirring and mixing as component A. Weigh 98 parts of Sulbang EVA resin, 0.51 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.53 parts of triallyl cyanurate, 0.25 parts of vinyl triacetoxysilane, 0.32 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 0.43 parts of bis-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate, and place them in a mixing kettle for stirring and mixing as component B.

[0062] The mixed materials are melted and plasticized by different single-screw extruders and extruded into three-layer films, in which component A is used as the middle layer and component B is used as the two side layers. After embossing, pulling and winding, a roll of packaging film is obtained, with a film thickness of 0.4mm, including a middle layer of 0.2mm and a thickness of 0.1mm on both sides.

[0063] Example 2

[0064]

[0065] Preparation of acid-binding ultraviolet light-converting agent B: 2-bromo-4,6-diphenyl-1,3,5-triazine (5.01 g), 4-aminophenylboronic acid pinacol ester (4.56 g), tetrakis(triphenylphosphine)palladium (0.37 g), potassium carbonate (5.53 g), tetrahydrofuran (85.00 ml) and water (20 ml) were added to a three-necked glass flask, fully degassed with nitrogen for multiple times, and filled with nitrogen, heated to 88°C, and reacted for 48 hours under stirring. The reaction solution was cooled to room temperature, then washed and extracted with dichloromethane and saturated sodium chloride aqueous solution, and then the organic phase was dried with anhydrous sodium sulfate, and the solvent was removed under reduced pressure. The obtained solid was dispersed with ethyl acetate / acetonitrile mixed solution, filtered, and then recrystallized and purified to obtain 2.79 g (yield 53.7%) of acid-binding ultraviolet light-converting agent B.

[0066] Masterbatch preparation: Acid-binding UV conversion agent B and EVA particles with a melt index of 25 g / 10 min and a vinyl acetate content of 28% were fully mixed in a mass ratio of 10:90, melt-plasticized and extruded into granules at a temperature of 95° C. using a twin-screw extruder to prepare a 10% concentration of acid-binding UV conversion agent masterbatch 2.

[0067] Film preparation: Weigh 5 parts of acid-bound UV light conversion agent masterbatch 1, 93 parts of Sailbon EVA resin, 0.51 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.53 parts of triallyl cyanurate, 0.25 parts of vinyl triacetoxysilane, 0.32 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 0.43 parts of di-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate, and place them in a mixing kettle for stirring and mixing. The mixed materials are melted and plasticized by a single-screw extruder, extruded into a single-layer film, and embossed, pulled, and rolled to obtain a rolled packaging film with a film thickness of 0.4 mm.

[0068] Example 3

[0069]

[0070] Preparation of acid-binding ultraviolet light-converting agent C: 2-amino-4,6-dichloro-1,3,5-triazine (3.01 g), 4-isobutylphenylboronic acid pinacol ester (10.87 g), tetrakis(triphenylphosphine)palladium (0.42 g), potassium carbonate (6.28 g), toluene (85 ml) and water (15 ml) were added to a three-necked glass flask, fully degassed with nitrogen for multiple times, and filled with nitrogen, heated to 90°C, and reacted for 48 hours under stirring. The reaction solution was cooled to room temperature, then washed and extracted with dichloromethane and saturated sodium chloride aqueous solution, and then the organic phase was dried with anhydrous sodium sulfate, and the solvent was removed under reduced pressure. The obtained solid was dispersed with dichloromethane, filtered, and then recrystallized and purified to obtain 2.46 g (yield 41.7%) of acid-binding ultraviolet light-converting agent C.

[0071] The following steps are the same as in Example 1.

[0072] Example 4

[0073] The difference from Example 1 is that

[0074] The structural formula of acid-binding type UV conversion agent B is as follows:

[0075]

[0076] The following steps are the same as in Example 1.

[0077] Example 5

[0078] The difference from Example 1 is that

[0079] The adhesive film in this embodiment is a single-layer structure:

[0080] Film preparation: Weigh 5 parts of acid-bound UV conversion agent masterbatch 1, 93 parts of Sailbon EVA resin, 0.51 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.53 parts of triallyl cyanurate, 0.25 parts of vinyl triacetoxysilane, 0.32 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.43 parts of bis-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate, place in a mixing kettle for stirring and mixing, melt and plasticize with a single-screw extruder, extrude into a film, and emboss, pull, and roll to obtain a rolled packaging film with a film thickness of 0.4 mm;

[0081] The following steps are the same as in Example 1.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that the structural formula of the ultraviolet light conversion agent is as follows:

[0084]

[0085] The following steps are the same as in Example 1.

[0086] Comparative Example 2

[0087] The difference from Example 1 is that the acid binding agent is magnesium hydroxide particles with an average particle size of 10 μm.

[0088] Masterbatch preparation: Magnesium hydroxide particles and EVA particles with a melt index of 25g / 10min and a vinyl acetate content of 28% are fully mixed in a mass ratio of 10:90, melt-plasticized and extruded into granules at a temperature of 95°C through a twin-screw extruder to prepare a 10% concentration of magnesium hydroxide dispersed masterbatch.

[0089] The following steps are the same as in Example 1.

[0090] Comparative Example 3

[0091] The difference from Example 1 is that no acid-binding type ultraviolet light conversion agent is added:

[0092] Film preparation: Weigh 98 parts of Sulbang EVA resin, 0.51 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.53 parts of triallyl cyanurate, 0.25 parts of vinyl triacetoxysilane, 0.32 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 0.43 parts of bis-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate, place them in a mixing kettle for stirring and mixing, melt and plasticize them with a single-screw extruder, extrude them into a film, and emboss, pull, and wind up to obtain a rolled packaging film with a film thickness of 0.4 mm.

[0093] Performance Test:

[0094] Light transmittance test: The cast film was hot-pressed at 145°C for 18 minutes to obtain a laminated film sample, and the light transmittance was tested according to the test method provided in GB / T29848-2018.

[0095] Photovoltaic module power: stack photovoltaic glass, encapsulation film, welded cells, encapsulation film, photovoltaic glass in this order, and then use a vacuum laminator for lamination at a lamination temperature of 145°C for 18 minutes. After cooling, the structure is as follows: Figure 3 For solar cell modules, conduct PV module current, voltage, initial power test, and power test after PID aging (unit: W).

[0096] PID test: stack photovoltaic glass, encapsulation film, welded cells, encapsulation film, photovoltaic glass in this order, and then use a vacuum laminator for lamination at a temperature of 145°C for 18 minutes, and then cool to obtain a solar panel. The PID test is conducted in accordance with IEC TS 62804-1:2015.

[0097] The test results are shown in Table 1.

[0098]

[0099]

[0100] Data Results

[0101] In the above test, comparative example 1 added a light conversion agent without acid binding function, comparative example 2 added an inorganic acid binding agent without light conversion function, and comparative example 3 did not add a common light conversion agent or acid binding. In contrast, examples 1 to 5 all have light conversion agents with acid binding function, and although example 5 has the same light conversion agent structure as example 1, it is a single-layer structure. Under the same total thickness, the single-layer film functional layer is thicker;

[0102] The test results reflect the advantages of the acid-binding ultraviolet light-converting agent very well. Comparative Example 2 with the addition of an inorganic acid-binding agent has the lowest transmittance in the visible light region, while the transmittances of other samples without the addition of an acid-binding agent and samples with the addition of an acid-binding ultraviolet light-converting agent in the visible light region are all above 90%; compared with Comparative Example 2 and Comparative Example 3 without the addition of an ultraviolet light-converting agent, the other samples all show lower transmittance in the ultraviolet region, while the power of the components is relatively high, which should be due to the light-converting effect of the light-converting agent on ultraviolet light; Comparative Examples 1 and Comparative Examples 3 without the addition of an acid-binding agent have obvious power attenuation of more than 7% after PID aging, while the samples with the addition of inorganic magnesium hydroxide particles also have relatively high attenuation, which may be due to the uneven dispersion of inorganic materials, while the samples with the addition of an acid-binding ultraviolet light-converting agent show relatively weak power attenuation.

[0103] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It should be particularly noted that all similar replacements and modifications are obvious to those skilled in the art, and they all fall within the scope of protection of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

Claims

1. An acid-binding ultraviolet wavelength conversion resin masterbatch, which comprises, by weight percentage, 80-99.8% of vinyl resin, 0.01-15% of acid-binding ultraviolet light conversion agent, and 0.18-10% of auxiliary agent.

2. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 1, characterized in that: The vinyl resin is a high molecular thermoplastic polymer material with a melting temperature of 65°C to 120°C.

3. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 1, characterized in that: The vinyl resin includes polyethylene, polypropylene, or a copolymer of ethylene and α-olefin, or a copolymer of ethylene and one or more of vinyl acetate, acrylic acid, acrylic ester, methacrylic acid, methacrylic ester, maleic anhydride, and glycidyl methacrylate. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 1 is characterized in that the acid-binding ultraviolet light conversion agent is a triazine derivative containing an active group, and its general structural formula is as follows: Wherein, R1, R2, and R3 are each independently selected from the group consisting of amino, amino-substituted or unsubstituted C1-C10 alkyl, Any one of the above, wherein R4 is selected from any one of hydrogen, amino, amino-substituted or unsubstituted C1-C10 alkyl.

4. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 1, characterized in that: The auxiliary agent is one or a mixture of two or more of an initiator, a crosslinking agent, a coupling agent, an antioxidant, and a stabilizer.

5. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The weight percentage of the initiator is 0.005-5%.

6. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The weight percentage of the cross-linking agent is 0.005-5%.

7. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The weight percentage of the coupling agent is 0.005-5%.

8. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The weight percentage of the antioxidant is 0.005-5%.

9. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The weight percentage of the stabilizer is 0.005-5%.

10. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The initiator is selected from one or two or more of a cationic polymerization initiator, a free radical polymerization initiator, an anionic polymerization initiator or a coordination polymerization initiator.

11. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The crosslinking agent is selected from substances containing multiple unsaturated double bonds.

12. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The coupling agent is selected from organic chromium complexes, silanes, titanates and aluminate compounds.

13. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The antioxidant is selected from free radical absorbing antioxidants, oxygen scavenging antioxidants, metal ion chelating stabilizing antioxidants, singlet oxygen capturing antioxidants, and biological antioxidants.

14. The acid-binding ultraviolet wavelength conversion resin masterbatch according to claim 4, characterized in that: The light stabilizer is selected from light shielding agents, ultraviolet absorbers, free radical scavengers, and hydroperoxide decomposers.

15. The method for preparing the acid-binding ultraviolet wavelength conversion resin masterbatch according to any one of claims 1 to 14, characterized in that: Several of the aforementioned acid-binding ultraviolet wavelength converter, light stabilizer, initiator, crosslinking agent, coupling agent, and antioxidant are mixed with vinyl resin, and then melt-plasticized and extruded by a screw granulator at 65° C. to 150° C. to obtain a granular material.

16. An acid-binding ultraviolet wavelength conversion composition comprising 70-98% of a vinyl resin, 1-15% of an acid-binding ultraviolet light-converting resin masterbatch according to any one of claims 1 to 14, and 1-7% of an auxiliary agent. 17 . A photovoltaic encapsulation film, which is a single-layer structure or a multi-layer structure, and the material of at least one layer of the encapsulation film is the acid-binding ultraviolet wavelength conversion composition according to claim 16 .

18. An acid-bound ultraviolet light conversion agent used in photovoltaic encapsulation film, which is a triazine derivative containing an active group, and its general structural formula is as follows: in, R1, R2, and R3 are each independently selected from amino, amino-substituted or unsubstituted C1-C10 alkyl, Any one of the above, wherein R4 is selected from any one of hydrogen, amino, amino-substituted or unsubstituted C1-C10 alkyl.

19. The method for preparing the acid-binding ultraviolet light conversion agent according to claim 18, which is obtained by using a triazine derivative containing a halogen group as a raw material and performing a substitution reaction under alkaline conditions and the presence of a catalyst.

20. An application of an acid-binding type ultraviolet light conversion agent in a photovoltaic encapsulation film, wherein the acid-binding type ultraviolet light conversion agent is a triazine derivative containing an active group, and its general structural formula is as follows: in, R1, R2, and R3 are each independently selected from amino, amino-substituted or unsubstituted C1-C10 alkyl, Any one of the above, wherein R4 is selected from any one of hydrogen, amino, amino-substituted or unsubstituted C1-C10 alkyl.

Citation Information

Patent Citations

  • Sealing films for solar cell

    CN101542748B

  • A sealing material composition for solar cells, a method for manufacturing the same, a sealing material layer for solar cells using the same, and a solar cell module.

    CN105308113B

  • Wavelength conversion encapsulation material composition, wavelength conversion encapsulation material layer, and solar cell module using the same.

    CN105684163B

  • Ultrahigh weather-resistant polyolefin film used for photovoltaic modules and preparation method

    CN108250576A

  • Special packaging adhesive film for TOPCon battery and preparation method of special packaging adhesive film

    CN114806457A